2023
DOI: 10.3390/ijms241411330
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of MicroRNA 21 in Osteogenesis: An Update

Abstract: MicroRNAs are short, single-stranded ribonucleic acids expressed endogenously in the body to regulate gene expression at the post-translational level, with exogenous microRNA offering an attractive approach to therapy. Among the myriad microRNA candidates involved in controlling bone homeostasis and remodeling, microRNA 21 (miR21) is the most abundant. This paper discusses the studies conducted on the role and mechanism of human miR21 (hsa-miR21) in the regulation of bones and the various pathways mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(94 reference statements)
0
1
0
Order By: Relevance
“… 18 In bone, miR21 has been shown to regulate both bone formation and bone resorption arms of bone remodeling. 19 We previously showed that deletion of miR21 from cells expressing an 8 kb fragment of the DMP1 promoter (mainly osteocytes) results in a sex-dependent phenotype, with reduced osteoblasts and osteoclasts in females (with no change in bone mass) and increased osteoblasts and osteoclasts in males (resulting in increased bone mass). 5 Further we showed that basal levels of miR21, as well as levels in miR21 ΔOt mice, are lower in calvaria bones from males compared to female mice.…”
Section: Discussionmentioning
confidence: 99%
“… 18 In bone, miR21 has been shown to regulate both bone formation and bone resorption arms of bone remodeling. 19 We previously showed that deletion of miR21 from cells expressing an 8 kb fragment of the DMP1 promoter (mainly osteocytes) results in a sex-dependent phenotype, with reduced osteoblasts and osteoclasts in females (with no change in bone mass) and increased osteoblasts and osteoclasts in males (resulting in increased bone mass). 5 Further we showed that basal levels of miR21, as well as levels in miR21 ΔOt mice, are lower in calvaria bones from males compared to female mice.…”
Section: Discussionmentioning
confidence: 99%
“…This homeostasis in bone remodeling is maintained via bone resorption by osteoclasts and bone formation by osteoblasts, which are maintained by the RANKL, SMAD1, DICER1, and Wnt signaling pathways, as described in the current study. SMAD is an intracellular signaling protein which phosphorylates transforming growth factor(TGF)-β and bone morphogenic proteins (BMPs); these act on transcription factors like RUNX2 and Osx, which are crucial in the osteogenic differentiation of MSCs [18,22,36]. The current study has shown a higher mRNA expression of SMAD1 with lower doses of LPS (3.125, 6.25, 12.5 µg/mL), indicating the increase in bone formation, but RUNX2, which is key transcription factor, was insignificant: this shows the incongruity of this factor with the intracellular signaling molecule (SMAD1).…”
Section: Bone Formation and Resorptionmentioning
confidence: 99%